Towards an Association of Caribbean States : raising some awkward questions. - SERBIN, Andres (1994)
Traces the history of ACS. Reviews each of the relevant actors and subregional groups involved, along with their assorted linkages (both regional and extra-regional), in order to ascertain the difficulties that confront the regionalization process in general, and the functioning of the ACS in particular.